2001
DOI: 10.1093/hsw/26.4.257
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregiving and Traumatic Brain Injury

Abstract: This article discusses the extensive challenges faced by those providing long-term care for family members with traumatic brain injury. Areas reviewed include the nature of care needs, stress and burden experienced, and how families cope with caregiving demands. This article concludes with a discussion of what social workers can do to reduce the demands of family caregiving and subsequently, improve caregivers' quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 24 publications
2
69
0
2
Order By: Relevance
“…This type of involvement is congruent with the results presented by Ishikawa et al (2012), which identified that spending time with and providing care for the patient with a TBI are important elements of the family experience. Some examples of care provision were highlighted in Degeneffe's (2001) study and found that the duties that family caregivers undertake can be extensive and may include assistance with ADLs and medication administration, among other responsibilities.…”
Section: Qualitative Themesmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of involvement is congruent with the results presented by Ishikawa et al (2012), which identified that spending time with and providing care for the patient with a TBI are important elements of the family experience. Some examples of care provision were highlighted in Degeneffe's (2001) study and found that the duties that family caregivers undertake can be extensive and may include assistance with ADLs and medication administration, among other responsibilities.…”
Section: Qualitative Themesmentioning
confidence: 99%
“…Family members often experience significant distress and compromised quality of life in the wake of the neurobehavioral changes imposed by TBI (Rivera, Elliott, Berry, & Grant, 2008). Family members typically face high levels of stress, burden, social isolation, role changes, and other psychosocial health problems that generally do not lessen with time (Barclay, 2013;Degeneffe, 2001). The challenges and distress experienced by family members can impact the rehabilitation process as well as the recovery of the person with TBI (Sander, 2014).…”
mentioning
confidence: 99%
“…En effet, de nombreuses études se sont penchées sur les impacts de l'annonce d'un diagnostic de DP sur les proches de la personne atteinte O'Connell et al, 2004 ;Mann, 2002 ;Degeneffe, 2001) et démontrent qu'il importe de les soutenir eux aussi afin de favoriser le mieux-être de chaque membre du système familial. Cependant, nous constatons que les étapes qu'ils traversent pour s'adapter à la nouvelle situation ont été moins documentées que celles parcourues par la personne atteinte.…”
Section: Frontières ⁄ Vol 22 N Os 1-2unclassified
“…En effet, il revient souvent aux familles d'assumer en partie les soins à prodiguer, sans que celles-ci aient les ressources suffisantes et les connaissances nécessaires pour y parvenir (O'Connell et al, 2004 ;Degeneffe, 2001). Ainsi, les familles ont besoin d'une aide professionnelle pour prendre certaines décisions concernant la personne ayant une DP (Bond et al, 2003).…”
Section: éTape 4 : Après La Réadaptationunclassified
“…Content areas in qualitative studies include clear, timely, and accurate information on diagnosis; treatment plans; prognosis and course of recovery; best-and worstcase scenarios; reasons for and results of diagnostic studies; specific hospital equipment use; medications; rationale for treatments; and possible patient behavior changes [26][27][28]. Caregivers also want to understand the purpose of rehabilitation [29], how rehabilitation facilitates recovery [30], and the effect that caring for a patient with TBI has on family relationships [31]. Information on community support, financial assistance, and self-care is needed as well [29,[32][33].…”
Section: Type Of Information Neededmentioning
confidence: 99%